t=-13+(-3)

Simple and best practice solution for t=-13+(-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for t=-13+(-3) equation:


Simplifying
t = -13 + (-3)
t = -13 + -3

Combine like terms: -13 + -3 = -16
t = -16

Solving
t = -16

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Simplifying
t = -16

See similar equations:

| y=2.4x-0.001x^2 | | 2b=90 | | 8sin^2x=5-10cosx | | 4x-8(x+1)=-4x+24 | | 8/m=4 | | .4x+.25(81-x)=30 | | 8(x-7)-3(2x+y)=15 | | x^2-5x+4x=180 | | 5x-25=18-4x+5-3x | | 8senx-3cosx=0 | | Y+15y+36=0 | | 2x+15=-2x-5 | | -3y-9y=4/5 | | 8x^2-5x-8=0 | | 4(y-9)=-6(5+y) | | 6x-52=3x | | 0.66q+0.75=0.5 | | 4(x+3)=-5 | | 8x+15+3x+20= | | 15+y=2y-7 | | 12/35=6/7n | | 7a+25=60+2a | | -14x=-5x+36 | | s-35=20 | | 30r^3+85r^2-70r= | | 6-(2-4x)+5=3(1-3x) | | 27+4x=7 | | 3x-t=2x | | r+31=-3(1-6r) | | -2(-2x+3)=-10x-8 | | 4x-1=-2x+7 | | 6x+4(-3x-4)=44 |

Equations solver categories